The IPO performance of companies listed on the JSE alternative exchange - Mashaba, Thuthuka (My University, 2014)
The listing of firms on stock exchanges does not only provide these firms with the opportunity to raise long-term equity capital, it also allows for investors to participate in the primary and secondary equity markets. Traditionally executed through Initial Public Offerings (IPOs), listings were previously reserved for large firms due to the requirements and costs involved. In response, the Johannesburg Stock Exchange (JSE) introduced the JSE Alternative Exchange (AltX) in 2003 as a parallel exchange market in order to also provide South African small and medium sized entities with an opportunity to access equity capital. This also allowed for investors to invest in small high-growth companies with the expectation of higher returns. The aim of this research was to analyse the IPO performances of JSE AltX listings in order to establish the returns achieved by the initial IPO and the subsequent aftermarket participants. This research analysed the initial IPO returns attributable to the initial investors and the 1, 2 and 3 year aftermarket returns attributable to the aftermarket participants. Although various studies have been concluded on the investor returns for IPOs listing on the JSE, this report focused specifically on the AltX which has not been as extensively studied. IPOs listing on the JSE AltX from April 2006 to December 2011 were analysed. It was found that during this period, the average initial market-adjusted return offered to the initial invertors was 21 per cent after the first day of trade. The average 1, 2 and 3 year aftermarket market-adjusted returns were -0.08, -0.33 and 3.36 per cent respectively. An analysis of the combined aftermarket market-adjusted returns for the same 1, 2 and 3 year post IPO periods yielded returns of 25.17, 20.03 and 25.67 per cent respectively. From the conducted study, the results indicate that there is existence of average positive abnormal initial returns on the JSE AtlX, and returns underperformance for the two years following that. The aftermarket returns are then positive 3 years post IPO date. Combined returns were found to be abnormal and positive throughout the 1,2 and 3 year periods post IPO.
Keywords: Johannesburg Stock Exchange; JSE Alternative Exchange; Initial Public Offerings; Investor returns